Strategi Pembelajaran Pengendalian Diri Dalam Meningkatkan Karakter Tawadhu Peserta Didik Pada Mata Pelajaran PAI Di SMP Ciledug Al Musaddadiyah Garut - Salamudin, Ceceng; Lestari, Intan Pujiawati (STAI Al-Musaddadiyah Garut, 2023)
The character of humility (tawadhu) is crucial, especially for students within the school environment. However, there has been an observed deficiency in humility among students, manifesting in behaviors such as disrespectful speech, disobedience to teachers and parents, lack of diligence in studying, and untidy dressing. The Self-Control Learning Strategy is proposed as an effective solution to enhance the humility character of students. The objectives of this research are to describe: the level of humility character in students, the application of the self-control learning strategy, and the implications of this strategy on the humility character of students in Islamic Religious Education (PAI) at SMP Ciledug Al-Musaddadiyah Garut. This study employs a field research approach with a qualitative methodology. Data were collected through interviews, observations, and document studies involving the school principal, PAI teachers, guidance counselors, and students. The data analysis technique includes several stages: data reduction, data presentation, and drawing conclusions. The results of the research indicate that, at SMP Ciledug Al-Musaddadiyah Garut, after implementing the self-control learning strategy, which includes initiatives led by the school principal, PAI teachers, and the promotion of positive habits such as collective Dhuha prayers, memorization of Juz 30, and advice on the importance of humility, there has been a significant improvement in the students' humility character. Approximately 75% of the students have shown enhanced humility as a result of this strategy. Keywords : Self-Control Learning Strategy, Humility Character (Tawadhu), Islamic Religious Education (PAI)